Factors controlling the accelerated expansion of Imja Lake, Mount Everest region, Nepal. Issue 71 (March 2016) - Thakuri, Sudeep; Salerno, Franco; Bolch, Tobias; Guyennon, Nicolas; Tartari, Gianni
Abstract: This study explores the link between area increase of Imja Tsho (Lake) and changes of Imja Glacier (area ~25km 2 ) under the influence of climate change using multitemporal satellite imagery and local climate data. Between 1962 and 2013, Imja Lake expanded from 0.03±0.01 to 1.35±0.05 km 2 at a rate of 0.026±0.001 km 2 a -1 . The mean glacier-wide flow velocity was 37±30ma -1 during 1992–93 and 23±15ma -1 during 2013–14, indicating a decreasing velocity. A mean elevation change of –1.29±0.71ma -1 was observed over the lower part of the glacier in the period 2001–14, with a rate of –1.06±0.63ma -1 in 2001–08 and –1.56±0.80ma -1 in 2008–14. We conclude that the decrease in flow velocity is mainly associated with reduced accumulation due to a decrease in precipitation during the last few decades. Furthermore, glacier ablation has increased due to increasing maximum temperatures during the post-monsoon months. Decreased glacier flow velocities and increased mass losses induce the formation and subsequent expansion of glacial lakes under favourable topographic conditions.